ANALYZING THE QUALITY INSPECTION OF SPECIALTY COFFEE HOUSES IN TOMOHON - Gian Azaria Tenda; Joy E. Tulung; Regina T. Saerang (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
This condition regarding coffee shops become problematic because it created confusions for the customers that want to enjoy different types of coffees; regardless of the types of coffee shops run by the owners. In the end quality check need to be done and quality inspection with the criteria and standards need to be uphold for the best interest of the customers. The purpose of this study is to quality inspection of specialty coffee houses in Tomohon. This study uses a qualitative method and interview toward informants were conducted in order to gain information regarding the phenomenon. The result shows that quality inspection which constructed by 4 aspects of standard, measurement, testing, and characteristics are important for the betterment of the coffee shops. For coffee shop owners it is imperative to include all the mentioned indicators in quality inspections in order to reap the long-term benefits. Determining the correct parameter also important in order to make the quality parameters realistically achievable.   Keyword: quality inspection